Exchange of Total Carbohydrate, Minerals, and Phenolics in Grape and Grape Products - Özlem Aras Aşcı; Nilgün Göktürk Baydar (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to determine the total carbohydrate (CHO), minerals and phenolic (total phenolic content, total flavanols, total flavonols, and anthocyanins) of grape and grape products. For this reason, fresh grapes (Kalecik Karası, Öküzgözü, Emir, and Narince), raisins (Karadimrit and Sultani Çekirdeksiz), wines (Kalecik Karası, Öküzgözü, Emir, and Narince), commercial red grape juice, molasses, and vinegar were used as research materials. In conclusion, total CHO contents in the samples were ranged from 0.14 to 48.37 g 100 g-1. In terms of the minerals, molasses was rich in K while the highest contents of P and Fe were found in vinegar. Raisin of Karadimrit contained the highest Ca content among all the samples tested. Not only total phenolic contents but also total flavanols, total flavonols, and anthocyanins were altered depending on the sample types and the varieties. As a result, it was determined that grape and grape products represent a potentially significant source of CHO, minerals, and phenolic.